Navigating the Pathway to Care in Adults With Cerebral Palsy - Hurvitz, Edward A.; Whitney, Daniel G.; Waldron-Perrine, Brigid; Ryan, Dayna; Haapala, Heidi J.; Schmidt, Mary; Gray, Cathryn; Peterson, Mark D. (Frontiers in Neurology, 2021)
As individuals with cerebral palsy (CP) age, they face unique challenges which complicate their ability to access and receive appropriate health care. These problems exist at the level of the health care system, the clinician, and the individual. At the system level, there is an inadequate number of professionals who are informed of and interested in the care of adults with CP. Pediatric clinicians prefer treating children, and adult caregivers are not knowledgeable about and may feel less competent about CP. Pediatric care does not translate well to the adult population, and information about best practices for adults is just starting to develop. Differences in the physiologic development of individuals with CP render well-established clinical protocols for risk screening of chronic diseases less effective. Moreover, lack of supportive resources decreases a caregiver’s sense of self-efficacy in treating this population. The patient’s ability to navigate these barriers is complicated by the high prevalence of comorbid cognitive impairment and mental health issues including anxiety, depression, and other psychiatric disorders; a bidirectional relationship between challenges in navigating care/needs and comorbid mental health conditions appears likely. Many patients have additional barriers related to social determinants of health, such as access to transportation, accessible health care facilities, and other personal and environmental factors that may impede health maintenance and wellness. Increasing and disseminating knowledge, harnessing the power of new technologies such as telemedicine, and addressing mental health issues are some of the methods that are available to help adults with CP navigate this road.